At skabe folkehelte - Klapp, Orrin (Slagmark - Tidsskrift for idéhistorie, 2018)
The popular hero is a social type having certain definable roles. The problem of making a hero is that of imputing to a person these roles and of maintaining and building a collective interpretation which has the character of a legend. The destroying of a hero is the casting of him in antiheroic roles. Social types, especially fundamental symbols such as the hero, the villain, and the fool, provide a key to collective psychology because the mass recognizes and readily responds to these symbols.